1972
DOI: 10.1121/1.1981861
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Cutting of Rock Materials

Abstract: Low-frequency reciprocatory-rotary motion is imparted to a conventional axially vibrated ultrasonic cutter (18 kHz) that is impregnated with diamond grit of average size 0.003 in. The rotary motion is in a plane normal to the cutter axis. Cutting rates in rock materials of 10 ft/h are exceeded for 1-in. diam circular holes drilled to depths greater than 1 ft. Peak axial amplitude was 1.6 mil and the rotary motion was less than three to-and-fro oscillations per minute. Specific energy of the cutting process was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research was reported where a low-frequency reciprocatory-rotary movement was imparted to an 18 kHz longitudinal ultrasonic cutter [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research was reported where a low-frequency reciprocatory-rotary movement was imparted to an 18 kHz longitudinal ultrasonic cutter [6].…”
Section: Introductionmentioning
confidence: 99%